Gambaran Penggunaan Terapi Kombinasi Oral Metformin-Sulfonilurea pada Pasien DM Tipe 2 di Denpasar - Ida Ayu Amanda Dewi Wikannanda; Ni Luh Putu Eka Kartika Sari; Anak Agung Sri Agung Aryastuti (Aesculapius Medical Journal, 2023)
Type 2 diabetes mellitus (T2DM) is a global health problem in the form of metabolic disorder characterized by hyperglycemia. Management of T2DM includes pharmacological therapy with oral antidiabetic drugs, either monotherapy or combination therapy. Metformin and sulfonylureas combination therapy is the most common therapy given to T2DM patients in Indonesia, but studies on the use of this combination are limited. This study aims to provide an illustration of the use of metformin-sulfonylureas oral combination therapy in T2DM patients in Denpasar. This is a descriptive cross-sectional study, which was conducted in RSUD Bali Mandara, RSUD Wangaya Denpasar, and RSU Puri Raharja, using data from medical records from January 2020 – August 2021. The total amount of sample is 80 samples. Data that has been analyzed univariately is presented as narratives and tables. The characteristic of the samples includes age 46-65 years (73.8%), female gender (51.2%), having high school education (58.8%), working as private employee (50%), DM duration of 1-4 years (56.3%), and having 2-3 comorbidities (62.5%) with the most common comorbidity being hypertension (58.8%). Result showed that metformin-glimepiride was the most used type of metformin-sulfonylurea combination therapy among samples (90%), with the most used doses were 500 mg of metformin twice daily and 2 mg of glimepiride once daily (17,5%). Most of the samples have controlled level of FBG (60%), dominated by samples who used metformin-glimepiride combination therapy (63,9%). Metformin-glimepiride combination is the most common oral combination therapy due to better safety profile and ability to manage glucose levels than other sulfonylureas.